The Analysis of American Slang in Movie Script “The Wolf of Wall Street” - Aristya Dewi, Putu; Suastra, I Made (Humanis; Vol 22 No 1 (2018), 2018)
This study is entitled “The Analysis of American Slang Found in The Movie Script “The Wolf of Wall Street””. The aims of this study are to find out whether primary and secondary slang was used by the characters in movie script titled “The Wolf of Wall Street”, to find out the types and also the meaning of the slang word that used by the characters based on the context of the situation. Documentary method was used to collect the data and then qualitatively described base on the theory of Chapman (2007) who divided the types of slang into primary and secondary slang. This study also uses the theory of Leech (198i) who classified the types of meaning into seven types which are conceptual meaning, connotative meaning, social meaning, affective meaning, reflected meaning, collocative meaning, and thematic meaning. From the analysis, it can be concluded that primary slang was mostly found and used by the characters in the movie, but nevertheless there are several secondary slang used by the characters in “The Wolf of Wall Street” movie script due to a matter of stylistics choice and also used to describe things in a secret way. Among the seven types of meaning, there are only conceptual meaning, reflected meaning, and affective meaning. The meaning behind each slang word in “The Wolf of Wall Street” movie script are depend on the context in which slang words are used.